2014
DOI: 10.1111/jhn.12210
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of protein‐supplemented hospital food on protein intake in patients at nutritional risk: a randomised controlled trial

Abstract: The novel food service concept had a significant positive impact on overall protein intake and on weight-adjusted energy intake in hospitalised patients at nutritional risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 24 publications
3
69
0
Order By: Relevance
“…In a hospital setting, short-term options, such as replacing regular food products with enriched food products and meals, have shown to effectively increase intake [19][20][21]. Another option is to stimulate intake by 'nudging' , an example of nudging in the hospital setting was a study by van der Zanden et al In this study, call centre employees asked a patient with every meal order if they would like a dairy, or other protein-rich, product with their meal.…”
Section: Discussionmentioning
confidence: 99%
“…In a hospital setting, short-term options, such as replacing regular food products with enriched food products and meals, have shown to effectively increase intake [19][20][21]. Another option is to stimulate intake by 'nudging' , an example of nudging in the hospital setting was a study by van der Zanden et al In this study, call centre employees asked a patient with every meal order if they would like a dairy, or other protein-rich, product with their meal.…”
Section: Discussionmentioning
confidence: 99%
“…The nutrition intervention only lasted for a period of days, and the effect to hand grip strength has furthermore been questioned. 25 Health-related quality of life This study showed that HRQoL measured with the EQ5D-3L improved for both age groups below and above 70 years after intervention on nutrition and physical activity. Although EQ5D was not validated in infectious medical patients, it has been greatly supported in many other disease groups and is an amended tool in background population studies in Denmark.…”
Section: Discussionmentioning
confidence: 80%
“…Only grip strength, which was included as it has shown to be a significant predictor for evaluation of loss of function, did not show improvements. In the study by Munk et al, 25 the authors found that underpower may be one of the reasons why they did not detect differences between groups regarding hand grip strength and a 6-month nutrition intervention. This might also influence our results; however, only the 470-year olds show a trend to improvement.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore it is important to make such fortifications in collaboration with the kitchens chefs and, although time-consuming, it may be even beneficial to conduct a sensory evaluation. A recently published intervention study showed that a novel hospital menu which consisted of 23 small dishes enriched with high quality protein powder increased protein intake by around 10 g/d [25].…”
Section: Discussionmentioning
confidence: 99%